A model for personalized in vivo analysis of human immune responsiveness - Kalscheuer, Hannes (2012)
Studies of human immune diseases are generally limited to the analysis of peripheral blood lymphocytes of heterogenous patient populations. Improved models are needed to allow analysis of fundamental immunologic abnormalities predisposing to disease and in which to assess immunotherapies. Immunodeficient mice receiving human fetal thymus grafts and fetal CD34+ cells i.v. produce robust human immune systems, allowing analysis of human T cell development and function. However, to use humanized mice to study human immune-mediated disorders, immune sytsems must be generated from adult hematopoietic cells. Here, we demonstrated robust immune reconstitution in mice with hematopoietic stem cells (HSCs) aspirated from bone marrow of adults with Type 1 diabetes (T1D) and healthy control volunteers. In these humanized mice, cryopreservation of HLA allele-matched fetal thymic tissue prevented allogeneic adult HSC rejection. Newly generated T cells, which included regulatory T cells, were functional, self-tolerant, and had a diverse repertoire. The immune recognition of these mice mimicked that of the adult CD34+ cell donor, but the T cell phenotypes were more predominantly “naïve” than those of the adult donors. HSCs from T1D and control donors generated similar numbers of natural Tregs intrathymically; however, peripheral T cells from T1D subjects showed increased proportions of activated or memory cells compared to controls, suggesting possible HSC-intrinsic differences in T cell homeostasis that might underly immune pathology in T1D. This “Personalized Immune” (PI) mouse provides a new model for individualized analysis of human immune responses that may provide new insights into not only T1D, but other forms of immune function and dysfunction as well.